Evolution of stress testing of financial institutions - V. V. Kuznetsova; O. I. Larina (Управление)
The article raises the issues of developing a relevant tool for financial regulation and supervision – stress testing. Regulatory authorities use different types of testing to assess possible problems, as well as to model the response of supervised institutions to changes in system parameters. At present, the issues of ensuring financial stability are quite acute, and the search for effective analytical tools is an important managerial task, the solution of which is the focus of this study. The purpose of the article is to substantiate the advantages and limitations of this tool and to identify areas for its improvement. The evolution of the tool has been analyzed, and microprudential, macroprudential, and crisis stress tests investigated. The work is based on the data of the International Monetary Fund, as well as the Central Bank of the Russian Federation, the methods of analyzing regulatory documents and comparative economic analysis have been used. Types of stress tests and main stages of stress testing have been systematized. The authors, considering cross-border nature of financial institutions’ activities, conclude that transformation of supervisory tools is desirable and recommend the inclusion of non-banking financial organizations in stress testing, as well as network interactions between financial institutions as the main areas of improvement.